Androgen deprivation therapy plus abiraterone or docetaxel as neoadjuvant therapy for very-high-risk prostate cancer: a pooled analysis of two phase II trials - Zhuang, Junlong; Wang, Yuwen; Zhang, Shun; Fu, Yao; Huang, Haifeng; Lyu, Xiaoyu; Zhang, Shiwei; Marra, Giancarlo; Xu, Linfeng; Qiu, Xuefeng; Guo, Hongqian (Frontiers in Pharmacology, 2023)
Objective: The study aimed to compare the efficacy and safety of androgen deprivation therapy (ADT) with abiraterone or docetaxel versus ADT alone as neoadjuvant therapy in patients with very-high-risk localized prostate cancer. Methods: This was a pooled analysis of two single-center, randomized, controlled, phase II clinical trials (ClinicalTrials.gov: NCT04356430 and NCT04869371) conducted from December 2018 to March 2021. Eligible participants were randomly assigned to the intervention (ADT plus abiraterone or docetaxel) and control (ADT alone) groups at a 2:1 ratio. Efficacy was evaluated by pathological complete response (pCR), minimal residual disease (MRD), and 3-year biochemical progression-free survival (bPFS). Safety was also analyzed. Results: The study included 42 participants in the ADT group, 47 in the ADT plus docetaxel group, and 48 in the ADT plus abiraterone group. A total of 132 (96.4%) participants had very-high-risk prostate cancer, and 108 (78.8%) had locally advanced disease. The ADT plus docetaxel group (28%) and ADT plus abiraterone group (31%) had higher rates of pCR or MRD (p = 0.001 and p < 0.001) compared with the ADT group (2%). The 3-year bPFS was 41.9% (95% CI: 26.6–57.2), 51.1% (95% CI: 36.8–65.4), and 61.2% (95% CI: 45.5–76.9), respectively. Significant difference was found among groups in terms of bPFS (p = 0.037). Conclusion: Compared with ADT alone, neoadjuvant therapy with ADT plus docetaxel or abiraterone could achieve better pathological outcomes (pCR or MRD) for very-high-risk localized prostate cancer. The ADT plus abiraterone group showed longer bPFS than ADT alone. The combination regimens were tolerable.